Factors Associated with Caregiver Burden in Children With Cerebral Palsy in Developing Countries: A Systematic Review - Sanjaya, Kadek Dwi Wira; Wirawan, I Ketut Gede Agus Budi (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Cerebral palsy is a chronic condition requiring long-term care, leading to a high burden on caregivers, particularly in developing countries where access to cerebral palsy care remains inadequate. Objective: This study aims to identify factors influencing the burden on caregivers of children with cerebral palsy in developing countries. Methods: A systematic review following PRISMA was conducted. From inception to August 2024, 173 records were retrieved from PubMed and ScienceDirect. Studies were screened against predefined inclusion/exclusion criteria, and study and evidence quality were appraised. Results: A total of 10 articles were included. Depression, fatigue levels, and quality of life were identified as moderate-quality evidence for caregiver-related factors contributing to caregiver burden. GMFCS levels and spastic type were also identified as moderate-quality evidence for patient-related factors contributing to caregiver burden. Several factors with 'moderate' evidence quality include caregiver depression, fatigue levels, caregiver quality of life, GMFCS levels of cerebral palsy, and spastic type. Conclusion: Understanding these factors can guide the implementation of interventions to reduce caregiver burden, potentially improving caregivers' quality of life and positively impacting the care and therapy of patients with cerebral palsy.